Effect of MoS2 Concentration on Microstructure and Tribological Behavior of Electrophoretic-Electrodeposited Ni-Co-Al2O3-MoS2 Composites - Ya-gang Zhang; Wan-chang Sun; Min Ma; Sha-sha Tian; Yu-wan Liu; Yan Xiao (Materials Research, 2020)
Abstract Ni-Co-Al2O3-MoS2 composite coatings were prepared on the surface of LY12 aluminum alloys by electrophoresis-electrodeposition with different MoS2 concentrations. The microstructure, morphologies and composition of Ni-Co-Al2O3-MoS2 composites were characterized by X-ray diffractometer (XRD) and scanning electron microscopy (SEM) equipped with energy dispersive spectroscope (EDS). The micro-indentation hardness as well as friction and tribological properties of the coatings were tested by micro-hardness tester and friction and wear tester separately. Results revealed that the composite coating fabricated at 1.0 g⋅L-1 MoS2 achieved dense structure, and the average thickness of the coating was 39.820 µm. The micro-indentation hardness of the composite coating was decreased from 578 HV to 465 HV with the increase of MoS2 concentration. Also, the composite coating synthesized at 1.0 g·L-1 MoS2 had the lowest friction coefficient and wear rate.